Faktor Dominan Lansia Aktif Mengikuti Kegiatan Posyandu di Dusun Ngentak - Dita Anggraini; Zulpahiyana Zulpahiyana; Mulyanti Mulyanti (Alma Ata University Press, 2015)
Posyandu elderly aims to monitor the elderly condition in particular area because the body condition and aging process. But not all were able to actively follow the elderly Posyandu activities by various factors. The purpose of this study was to identify the factors related to the activity of the elderly following the Posyandu activities. This study was quantitative, using cross sectional design. From 155 respondents, 75 samples was obtained by purpossive sampling technique. Data were analyzed using chi-square test and logistic regression. Chi-square test result in this study indicate the variables that have a relationship with liveliness elderly family support variable (p=0.001), service cadres (p=0.000) and service of health workers (p=0.000). While that does not have a relationship with the activity of the elderly is a variable job (p=0.570) as well as distance and access (p=1.000). The result showed that cadre services was most dominant relationship with the liveliness of the elderly. In conclusion, the factors that have a relationship with the activity of the elderly following the Posyandu activities are support families, services and service cadres of health workers. This study sugest, cadres should be more active to disseminate information concerning the elderly and increase the number of cadres Posyandu.